Sex Differences in Mitochondrial Function Following a Controlled Cortical Impact Traumatic Brain Injury in Rodents - Kalimon, Olivia J.; Sullivan, Patrick G. (Frontiers in Molecular Neuroscience, 2021)
Traumatic brain injury (TBI) is a complex disease to study due to the multifactorial injury cascades occurring after the initial blow to the head. One of the most vital players in this secondary injury cascade, and therapeutic target of interest, is the mitochondrion. Mitochondria are important for the generation of cellular energy, regulation of cell death, and modulation of intracellular calcium which leaves these “powerhouses” especially susceptible to damage and dysfunction following traumatic brain injury. Most of the existing studies involving mitochondrial dysfunction after TBI have been performed in male rodent models, leaving a gap in knowledge on these same outcomes in females. This mini-review intends to highlight the available data on mitochondrial dysfunction in male and female rodents after controlled cortical impact (CCI) as a common model of TBI.